2023
DOI: 10.3390/su15021064
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological Analysis of Green Roofs Performance under a Mediterranean Climate: A Case Study in Lisbon, Portugal

Abstract: In this paper, the hydrological performance of eight pilot green roofs (GR) installed in Lisbon, Portugal, under a Mediterranean climate is analyzed. The pilot units were installed at Instituto Superior Técnico campus of Lisbon University. The pilots present different plant species and different substrate types, with some of the units incorporating recycled construction and demolition waste (RCW). The green roofs pilots’ hydrologic performance was evaluated through the simulation of artificial precipitation ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…Even so, the available rainwater volume is enough to supply the building's consumption for "other uses", excepting July to September. These results align with data obtained by [64,65] concerning the hydrological performance of GRs under the Mediterranean climate that showed water retention from 37 to 100% and from 12 to 100%, respectively. The reduction in RWHS performance associated with the installation of GR was also reported by [15,45], who claimed that combined systems may reduce RWHS efficiency in low rainfall climates, whereas in higher rainfall climates they may have a positive effect on RWHS efficiency as GR reduces excessive rainwater runoff.…”
Section: Proposed Measures and Its Impacts On Water Savingsupporting
confidence: 90%
“…Even so, the available rainwater volume is enough to supply the building's consumption for "other uses", excepting July to September. These results align with data obtained by [64,65] concerning the hydrological performance of GRs under the Mediterranean climate that showed water retention from 37 to 100% and from 12 to 100%, respectively. The reduction in RWHS performance associated with the installation of GR was also reported by [15,45], who claimed that combined systems may reduce RWHS efficiency in low rainfall climates, whereas in higher rainfall climates they may have a positive effect on RWHS efficiency as GR reduces excessive rainwater runoff.…”
Section: Proposed Measures and Its Impacts On Water Savingsupporting
confidence: 90%
“…It is a fact that conventional roofs allow rainwater to runoff their surfaces quickly, increasing flooding. GR, on the other hand, are considered to be of greater importance as they absorb rainwater, delaying its runoff and promoting evapotranspiration, increasing the effectiveness of stormwater management [12], as it is also shown in the studies [22,23,31,32]. Despite the urban allotment of only 2.1 ha, with the reduction of the maximum flow rate obtained, the impact of this NBS at the city level could be huge.…”
Section: Sizing the Public Stormwater Drainage Systemmentioning
confidence: 93%
“…A panoply of experimental studies have demonstrated, in several regions of the world and in different climates, the hydrological performance of GR in terms of control of rainwater runoff, sometimes in comparison with conventional roofs [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Noteworthy are two studies carried out in Lisbon, Portugal, under the Mediterranean climate, where the hydrological performance of GR was analyzed with favorable results in terms of runoff control, highlighting among other parameters, water retention from 37 to 100% in the study of Santos et al [31] and from 12 to 100% in the study of Brandão et al [32].…”
Section: Introductionmentioning
confidence: 99%
“…The plan has also considered decentralized blue-green solutions (e.g., stormwater source control techniques), such as the detention ponds of Alto da Ajuda and Ameixoeira, and involved not only physical construction measures, but also non-physical actions, such as knowledge acquisition through research [5], on capacity building, a monitoring and warning system, and public awareness campaigns. As major interventions for flooding control, two stormwater drainage tunnels have been built since 2022, both with 5.5 m diameter that will divert the stormwater flows of important tributaries areas of the main catchments directly to the Tagus River [6]. These tunnels will prevent the city downtown and most of the riverfront from frequent flooding events.…”
Section: Introductionmentioning
confidence: 99%